Attitudes and practices of public health academics towards research funding from for-profit organizations: Cross-sectional survey - Nakkash, Rima; Ali, Ahmed; Alaouie, Hala; Asmar, Khalil; Hirschhorn, Norbert; Mugharbil, Sanaa; Nuwayhid, Iman; London, Leslie; Saban, Amina; Rashid, Sabina Faiz; Ahmed, Md Koushik; Knai, Cecile; et al. (Springer Link, 2022)
This article was published in the International Journal of Public Health by Springer Link [Copyright © 2020, The Author(s)] and the definite version is available at: https://doi.org/10.1007/s00038-020-01416-0 The Journal's website is at: https://link.springer.com/article/10.1007/s00038-020-01416-0